2014
DOI: 10.1107/s2052252514002838
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity and isomorphic phase transition: a multi-temperature X-ray single-crystal and powder diffraction study of 1-(2′-aminophenyl)-2-methyl-4-nitroimidazole

Abstract: Multi-temperature single-crystal and powder diffraction experiments on 1-(2′-aminophenyl)-2-methyl-4-nitroimidazole show that this crystal undergoes an isomorphic phase transition with the coexistence of two phase domains over a wide temperature range. The anharmonic approach was the only way to model the resulting disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…Additionally, the refined anharmonic parameters appeared to be rather weakly correlated with multipolar parameters (the average correlation coefficient was equal to $ 0.5, the maximal was equal to 0.79 for the C 111 and Z -oriented dipole). These results are among many recent literature reports on this matter (Poulain et al, 2014;Herbst-Irmer et al, 2013;Zhurov et al, 2011;Scheins et al, 2010), where high-quality data allow for clear deconvolution of electron density and thermal motion features.…”
Section: Structure Solution and Refinementsupporting
confidence: 66%
See 1 more Smart Citation
“…Additionally, the refined anharmonic parameters appeared to be rather weakly correlated with multipolar parameters (the average correlation coefficient was equal to $ 0.5, the maximal was equal to 0.79 for the C 111 and Z -oriented dipole). These results are among many recent literature reports on this matter (Poulain et al, 2014;Herbst-Irmer et al, 2013;Zhurov et al, 2011;Scheins et al, 2010), where high-quality data allow for clear deconvolution of electron density and thermal motion features.…”
Section: Structure Solution and Refinementsupporting
confidence: 66%
“…As illustrated in Fig. 4(a), before the modelling a characteristic alternated residual density pattern (Herbst-Irmer et al, 2013;Poulain et al, 2014) at high-order data is clearly seen. Using only the third-order Gram-Charlier (GC) expansion parameters (Table 3), the anharmonic motion of the O atom was successfully modelled (Fig.…”
Section: Figurementioning
confidence: 85%
“…With the help of the fractal dimension plot and artificial data it was shown that neglect of third-order anharmonic motion leads to a characteristic (shashlik-like) pattern in the residual density . This imprint was also found in experimental data HerbstIrmer et al, 2013) and confirmed by other scientists [see, for example, Paul et al (2011) and Poulain et al (2014)]. …”
Section: Introductionsupporting
confidence: 82%
“…This data set corresponds to an anharmonic motion model refinement of the explosive RDX at 20 K (Zhurov et al, 2011). With increasing data quality, anharmonic motion models become more and more important in charge-density studies (see, for example, Meindl et al, 2010;Paul et al, 2011;Herbst-Irmer et al, 2013;Poulain et al, 2014;Jarzembska et al, 2014;Pinkerton et al, 2014, and many more).…”
Section: A Refinement With Few Systematic Errorsmentioning
confidence: 98%
“…A thorough study on the explosive 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) provided a good example in this respect [21], and it demonstrated the importance of anharmonic atomic displacement parameters (ADPs) for the determination of an accurate molecular electron density distribution (EDD) ρ(r). 2 Other more recent examples where anharmonicity was reported include the free radical p-(methylthio) phenyl nitronyl nitroxide [22], 1-(20-aminophenyl)-2-methyl-4-nitroimidazole [23] and the non-linear optical material 2-methyl-4-nitroaniline (MNA) [24].…”
Section: Introductionmentioning
confidence: 99%